2007
DOI: 10.1007/s10086-006-0816-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between charring rate and oxygen permeability for 12 different wood species

Abstract: The charring rates of 12 different wood species originating from Europe and the tropics with densities ranging from 350 to 750 kg/m 3 were investigated to obtain clues on their fire resistance behavior. This was done by measuring the thickness of the charred layer after a 30-min exposure to the standard fire ISO 834-1. No correlation was observed between charring rate and density. In search of another physical property that could be used as an indicator of fire resistance, the oxygen permeabilities of the sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 5 publications
1
54
0
Order By: Relevance
“…White [31] compared his results with test results from the literature, and did not find any correlation between density and charring rate for densities varying between 400 and 700 kg/m 3 . Hugi et al [40] also did not find any correlation between the charring rate and the density of the wood for a density range of 350-750 kg/m 3 . The lack of connection between the density and charring rate in these experiments might be due to variations in the density within one cross-section or along the length of a sample that may occur in wood, or it might be due to the small span in density for the sample ranges they tested.…”
Section: Densitymentioning
confidence: 92%
See 3 more Smart Citations
“…White [31] compared his results with test results from the literature, and did not find any correlation between density and charring rate for densities varying between 400 and 700 kg/m 3 . Hugi et al [40] also did not find any correlation between the charring rate and the density of the wood for a density range of 350-750 kg/m 3 . The lack of connection between the density and charring rate in these experiments might be due to variations in the density within one cross-section or along the length of a sample that may occur in wood, or it might be due to the small span in density for the sample ranges they tested.…”
Section: Densitymentioning
confidence: 92%
“…Hugi et al [40] found a strong correlation between the charring rate and the oxygen permeability of the wood; as the oxygen permeability decreased the charring rate also decreased.…”
Section: Permeabilitymentioning
confidence: 96%
See 2 more Smart Citations
“…Accordingly, a high curvature corresponds to a large deflection. The permeability of wood was measured at room temperature using a technique which was originally developed for concrete [20] and later adapted to wood [21]. By considering the common wood fibre orientation in perimeter elements of door frames and door leaves, only the permeability for oxygen perpendicular to the wood fibre direction was measured.…”
Section: Investigation Of Wooden Beamsmentioning
confidence: 99%